2013
DOI: 10.1200/jco.2013.31.15_suppl.e12022
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of first-line bevacizumab combined with paclitaxel in 220 patients with metastatic breast cancer: The Hungarian AVAREG observational study.

Abstract: e12022^ Background: First-line bevacizumab (Bev) combined with paclitaxel (Pac) significantly improves progression-free survival (PFS) and response rate vs. Pac alone in HER2-negative metastatic breast cancer (mBC), as shown in the E2100 study. The efficacy and safety of first-line Bev-Pac treatment was investigated in a non-interventional study in routine oncology practice in Hungary. Methods: Patients (pts) who had received no prior chemotherapy for mBC received Bev–Pac combination therapy according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
2
9
2
Order By: Relevance
“…It inhibits the growth of tumor cells. It is an important therapeutic drug in the treatment of a number of types of cancer, including breast cancer ( 29 ). It is known to stabilize microtubules during DNA synthesis, thereby suppressing mitosis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits the growth of tumor cells. It is an important therapeutic drug in the treatment of a number of types of cancer, including breast cancer ( 29 ). It is known to stabilize microtubules during DNA synthesis, thereby suppressing mitosis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent preclinical mouse tumor model mimicking postsurgical adjuvant or metastatic therapy, a VEGF pathway-targeting antibody drug (bevacizumab) with chemotherapy (paclitaxel) resulted in antitumor activity in a metastatic setting [ 72 ]. Based on these data and those already mentioned, preliminary clinical studies are ongoing and have shown some efficacy in the therapeutic role of targeting VEGF in combination with chemotherapy or radiation therapy [ 32 , 73 , 74 ].…”
Section: Brain Microenvironment and Breast Cancermentioning
confidence: 99%
“…Although several cohort studies have been carried out in other countries [8][9][10][11], clinical experience of bevacizumab plus paclitaxel combination therapy in Japan has been limited to the small number of patients in the JO19901 study, which enrolled 120 patients [7]. Therefore, we conducted a prospective multicenter observational study to investigate the effectiveness and safety of this combination as first-or second-line therapy for LA/mBC in daily clinical practice.…”
Section: Introductionmentioning
confidence: 99%